Pengaruh Kualitas Produk, Desain Produk, dan Promosi terhadap Keputusan Pembelian Produk di e-Commerce Lazada: (Studi Kasus pada Mahasiswa Yogyakarta) - Priandewi, Made Maitri; Fadhilah, Muinah; Maharani, Bernadetta Dian Septi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2022)
In the past, offline stores were in great demand by consumers. As technology develops, many companies develop and facilitate small online stores with the creation of E-Commerce. One of them is Lazada. This research was conducted to see the effect of product quality, product design, and promotion on purchasing decisions in Lazada E-Commerce, either simultaneously or partially. This research is descriptive with quantitative data. The data used are primary data obtained from questionnaires. The results of this study indicate that only partial testing of product quality (X1) and promotion (X3) variables has a significant effect on purchasing decisions (Y). Meanwhile, the product design variable (X2) has no significant effect on purchasing decisions (Y). Meanwhile, simultaneous testing of product quality (X1), product design (X2), and promotion (X3) has a joint effect on purchasing decisions (Y). Suggestions needed in further research are adding other variables that influence purchasing decisions, trust, features and so on.